The effect of food flavour on human appetite and eating behaviour - Yin, Wenting (2016)
Overconsumption of foods is thought to be one of the main causes of the rising number of global obesity. This thesis aims to investigate the role of food flavour in human appetite and eating behaviour through three studies. The first study investigated whether the sweetness intensity of a milkshake affected ad libitum intake of the milkshake and sensory-specific satiety (SSS). In a crossover single-blinded design, 24 participants consumed ad libitum high, ideal and low sweetness (HS, IS or LS) milkshakes over three visits. After milkshake intake, participants consumed ad libitum one, or both of a sweet and a savoury snack. All milkshake consumption was similar, suggesting that the sweetness intensity did not affect the ad libitum intake of the milkshake. After intake of all sweet milkshakes, ratings of desire for something sweet decreased, and subsequent savoury snacks were consumed more than subsequent sweet snacks. The sweetness intensity of milkshakes did not affect the change in the desire for something sweet or the subsequent snack intake. Ratings of desire for something savoury increased after the intake of HS milkshake and were higher than the ratings collected following the intake of IS milkshake. Therefore, this study suggested that a sweeter milkshake did not affect the magnitude of SSS for sweet foods, but increased a stronger sensory-specific appetite (SSA) for savoury foods. The second study examined the effects of aroma, taste and their interaction on subjective appetite sensation and subsequent lunch intake. In a crossover design, 26 females consumed 1 of the 4 test drinks as a preload: 1) water; 2) strawberry aroma in water; 3) sucrose and citric acid in water; 4) strawberry aroma, sucrose and citric acid in water. The subsequent lunch intake did not differ after all drink preloads. The drink with only aroma or only taste were not different from water in affecting appetite sensation. A drink with both aroma and taste reduced hunger ratings greater than water or a drink with only taste or aroma, during 15 min drinking and up to 30 min post drinking. Meanwhile, the drink with both taste and aroma was the highest in perceived flavour intensity. This suggests enhancing flavour perception of a drink through aroma-taste cross-modal interaction can increase the satiating effect of a drink. The third study investigated effects of sweetness, thickness and caramel flavour perception of custards on expected satiation and expected satiety of the custards. 90 participants (65 females, 25 males) tasted 18 custard samples over two sessions. Ingredients of custards were different only in the concentrations of caramel aroma, Truvia sweetener and carboxymethyl cellulose (CMC), based on an experimental design. Thickness enhanced both expected satiation and expected satiety. Sweetness enhanced expected satiation but not expected satiety. Caramel flavour did not affect expected satiation or expected satiety. The cognitive expectation on satiation and satiety has previously been shown to determine self-selected portion size. Therefore, the current study suggests that manipulating sweetness and thickness perception of a food without changing its energy content might help portion size control, via manipulating consumers’ cognitive expectation of the food. In conclusion, manipulating food flavour is a promising area to explore with the respect to hunger suppression and fullness enhancing, limiting the intake of eaten foods while promoting intake of other foods via SSS or SSA, and contributing to the cognitive control of portion size. Therefore, manipulation food flavour might be helpful for appetite control and supporting an energy-restrict diet; however, it seems challenging to reduce actual food energy intake through manipulating only the flavour properties of foods.